The Safety of Multimodality Monitoring Using a Triple-Lumen Bolt in Severe Acute Brain Injury - Bailey, Robert L.; Quattrone, Francis; Curtin, Colin; Frangos, Suzanne; Maloney-Wilensky, Eileen; Levine, Joshua M.; LeRoux, Peter D. (World neurosurgery, 2019)
Multimodality monitoring is used frequently to guide care of patients with severe acute brain injury. The aim of this study was to examine the safety and reliability of multimodality monitoring. From a prospective observational database at a Level I trauma center, 501 patients, including 300 men and 201 women (mean age 58 ± 39 years) were identified retrospectively. Each patient received a triple-lumen bolt and 3 monitors: intracranial pressure, brain temperature, and brain oxygen. Intensive care unit and hospital records were examined to identify complications, reasons for device replacement, malfunction and infection. Head computed tomography (CT) scans performed before and after the monitors were inserted were examined for evidence of monitor-related adverse effects. A total of 696 triple-lumen bolts were placed. Median duration of monitoring was 78.88 hours (interquartile range, 33.0–133.2 hours). Bilateral monitors were inserted in 22 (3.16%) patients. Ten (1.43%) monitors were replaced to allow magnetic resonance imaging, and 40 (5.74%) monitors were replaced to facilitate additional cranial surgery. Of 35 (5.02%) monitors that were replaced because they were thought to not be functioning properly, 19 (54.29%) were subsequently found to be functioning normally. Follow-up CT scans were compared with CT scans obtained before insertion of monitors; 9 (2.13%) small contusions and 10 (2.36%) extra-axial hematomas associated with the devices were identified. Based on the CT findings, the hematomas were thought to be associated with the insertion technique rather than the device; 4 hematomas required treatment. Twenty-two (3.16%) devices were incorrectly placed (e.g., the probe was in an infarct or an already existing contusion). Only 1 associated infection was identified. Placement of intracranial monitors for multimodality neuromonitoring using a triple-lumen bolt appears to be safe. The complication rate is similar to published complication rates for single-lumen bolts and single monitors.